The IMPACT OF LOYALTY MEDIATION ON THE WORK ENVIRONMENT AND COMPENSATION ON EMPLOYEE PERFORMANCE IN THE GENERAL SECTION OF THE REGIONAL SECRETARY (SEKDA) OF JEMBER REGENCY - Eka Martiana; Ni Nyoman Putu Martini; Feti Fatimah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of work environment and compensation on the performance of employees of the General Section of the Jember Regency Secretary with loyalty as a mediation variable. The work environment includes work atmosphere, relationships between co-workers, relationships with leaders, facilities, and physical hygiene. Compensation includes salary, bonuses, incentives, indirect compensation, and award benefits. The research uses a quantitative method with a survey approach and data analysis using statistical techniques to test the direct and indirect influences between variables. The results of the study showed that the work environment and compensation had a positive and significant effect on employee loyalty, which further mediated the influence of these two variables on significantly improving employee performance. A conducive work environment and adequate compensation form high employee loyalty that encourages productivity, work quality, and employee commitment in carrying out duties. In conclusion, improving the quality of the work environment and a fair and transparent compensation system are essential to building employee loyalty, which ultimately improves organizational performance. This study provides recommendations for the management of the Jember Regency Secretary to continue to develop and optimize these two aspects for better and sustainable public services.